C. G. Jung speaking : interviews and encounters - McGuire, William, 1917-2009; Hull, R. F. C. (Richard Francis Carrington), 1913-1974 (Bollingen series ;, 1977)
A collection of journalistic interviews which span Jung's lifetime. This book captures his personality and spirit in more than 50 accounts of talks and meetings with him. They range from transcripts of interviews for radio, television, and film to memoirs written by notable personalities.